Maximum acceptable work time for the upper limbs task and lower limbs task (2015)
The physical workload is a major occupational risk factor for workers. Currently the used methods to assess physical dynamic work load only consider working with the whole body and do not discriminate the load on each of the body segments. Determine the maximum acceptable dynamic work time when the work involves the whole body, the upper limbs and the lower limbs. Heart rate and oxygen consumption measured by ergospirometry were monitored in 30 workers exposed to various loads executed with the whole body, legs and upper limbs. Anaerobic threshold was determined by respiratory quotient. This was used to calculate the acceptable dynamic work time. Statistically significant differences between acceptable dynamic work time for upper limbs and lower limbs were found. A negative exponential correlation was found between the work load time, the oxygen consumption and the heart rate. R> 0.9 in all cases. Six regression equations were proposed to determine the acceptable dynamic work time. The acceptable dynamic work time for lower limbs and whole body was similar. The acceptable dynamic work time for upper limbs was significantly lower than acceptable dynamic whole body work time. The relative heart rate seems to be the best indicator to measure acceptable dynamic work time. © 2015